Relationships Are the Intervention: An Interview With Michael Marlowe. (May 2023) - Poling, Daniel V.; Van Loan, Christopher L.; Garwood, Justin D.
Dr. Michael J. Marlowe is emeritus professor of special education in the College of Education at Appalachian State University. An English graduate from the University of Kentucky, he has a PhD in special education from the University of Florida and a MS degree in elementary education from Indiana University.